Ghana : 2008 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Ghana. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This 2008 Article IV Consultation highlights that Ghana's growth has remained strong, fuelled by both the private and public sectors. The Ghanaian economy maintained strong growth of about 6 1\2 percent in 2007 and the first months of 2008. The private sector has responded positively to macroeconomic stability, structural reforms, and an increasingly business-friendly environment. But fiscal spending also increased, leading to excess demand. Supply-side shocks, especially from international fuel prices, have impacted Ghana negatively, although overall, Ghana's terms of trade continued to improve.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet